Evaluasi Usability dan Fungsionalitas Website Siuber Universitas Palangkaraya: Pendekatan Black Box dan System Usability Scale - Parhusip, Jadiaman; Arrbiyannoor ilham Sanusie, Arbiyanoor (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The SIUBER Information System is a vital instrument in supporting academic activities at universities. However, technical challenges such as unstable access are frequently complained about by users. This study aims to evaluate the quality of the SIUBER website using two approaches: Black Box Testing to validate technical functions and the System Usability Scale (SUS) to measure user satisfaction. Data was collected from 20 active user respondents. Black Box testing results indicated that functional features functioned 100% effectively, but stability issues were found under high access loads. The usability measurement results yielded an average conversion score of 62.5 (Acceptable Category - Grade D). In-depth analysis revealed a disparity: the interface design score was very high (3.89/5), while the stability score was very low (2.63/5). This study concluded that the primary issue with SIUBER was not the interface, but rather the server infrastructure, recommending hardware improvements as a top priority